Dekonstruksi Ruang Domestik Dalam Film Ki & Ka - Amalia, Desi; Tiara, Wan; Sazali, Hasan; Andinata, Maulana (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research was conducted with the aim of deconstructing gender roles in the domestic space using a Bollywood film entitled Ki & Ka, with the binary opposition of patriarchal culture that is, deconstructing is carried out by reserving the binary opposition. This research is a type of qualitative descriptive research with the method used in analyzing the data is descriptive analysis with the theoretical perspective of Jaques Derrida's deconstruction. The results of the study show that the deconstruction in the film Ki & Ka has succeeded in making Kabir fulfill his role as the controller of domestic space in his household with Kia. Keywords: deconstruction, binary opotition, gender